Expert and novice sensitivity to environmental regularities in predicting NFL games - Lauren E. Montgomery; Michael D. Lee (Judgment and Decision Making, 2021)
We study whether experts and novices differ in the way they make predictions about National Football League games. In particular, we measure to what extent their predictions are consistent with five environmental regularities that could support decision making based on heuristics. These regularities involve the home team winning more often, the team with the better win-loss record winning more often, the team favored by the majority of media experts winning more often, and two others related to surprise wins and losses in the teams’ previous game. Using signal detection theory and hierarchical Bayesian analysis, we show that expert predictions for the 2017 National Football League (NFL) season generally follow these regularities in a near optimal way, but novice predictions do not. These results support the idea that using heuristics adapted to the decision environment can support accurate predictions and be an indicator of expertise.